Thermal evolution of Cathaysian block along the South China margin since the Late Cretaceous: evidence from low-temperature thermochronology - Shi, Hongcai; Xie, Hui; Zhao, Weina; Liu, Tangwei; Kong, Deming; Bao, Chuang; Liu, Lijie (Frontiers in Earth Science, 2025)
The Cathaysian Block has undergone complex tectonic transformation since the Mesozoic, with significant topographic and geomorphological changes due to large-scale magmatism, as well as tectonism in the central area. Apatite fission track (AFT) and zircon (U-Th)/He (ZHe) data were used to reveal the tectonic-thermal evolution history of the southeastern margin of the Cathaysian Block in the coastal region during the Late Cretaceous in this paper. Results suggest AFT ages range between 36.3 ± 2.7 Ma and 63.5 ± 6.7 Ma with mean confined track lengths from 12.99 ± 1.54 µm to 13.7 ± 1.54 µm. ZHe ages are ranged from 72.6 ± 4.5 to 113.3 ± 7.0 Ma and concentrated in 90-100 Ma. Thermal history modeling indicated a multi-stage cooling history: (1) Widespread Late Cretaceous to Paleocene cooling across the entire coastal mountain. The Late Cretaceous cooling was coincident with rollback of the subducted paleo-Pacific Plate, which resulted in a negative inversion from compression to extension. (2A) rapid cooling beginning at ∼60 Ma and at ∼45 Ma, which was interpreted as temporally coinciding with continental rifting along the Cathaysian coastal margin, considered to have signaled the opening of the South China Sea (SCS); and (2B) a subsequent slow cooling stage with a small temperature change at ∼50°C–65°C during the Oligocene to middle Miocene, accompanied by migration of the central rift to the marine basin. (3) A final stage of rapid cooling to surface temperature commencing about 18 and 10 Ma since the Miocene in response to multiple-plates interaction caused by the Tibetan Plateau uplift and the collision of the Philippine Block with the Eurasian continent.